Changing trends in mortality among solid organ transplant recipients hospitalized for COVID-19 during the course of the pandemic - VELİOĞLU, ARZU (WILEY, 2022)
Mortality among patients hospitalized for COVID-19 has declined over the course of the pandemic. Mortality trends specifically in solid organ transplant recipients (SOTR) are unknown. Using data from a multicenter registry of SOTR hospitalized for COVID-19, we compared 28-day mortality between early 2020 (March 1, 2020-June 19, 2020) and late 2020 (June 20, 2020-December 31, 2020). Multivariable logistic regression was used to assess comorbidity-adjusted mortality. Time period of diagnosis was available for 1435/1616 (88.8%) SOTR and 971/1435 (67.7%) were hospitalized: 571/753 (75.8%) in early 2020 and 402/682 (58.9%) in late 2020 (p < .001). Crude 28-day mortality decreased between the early and late periods (112/571 [19.6%] vs. 55/402 [13.7%]) and remained lower in the late period even after adjusting for baseline comorbidities (aOR 0.67, 95% CI 0.46-0.98, p = .016). Between the early and late periods, the use of corticosteroids (>= 6 mg dexamethasone/day) and remdesivir increased (62/571 [10.9%] vs. 243/402 [61.5%], p < .001 and 50/571 [8.8%] vs. 213/402 [52.2%], p < .001, respectively), and the use of hydroxychloroquine and IL-6/IL-6 receptor inhibitor decreased (329/571 [60.0%] vs. 4/492 [1.0%], p < .001 and 73/571 [12.8%] vs. 5/402 [1.2%], p < .001, respectively). Mortality among SOTR hospitalized for COVID-19 declined between early and late 2020, consistent with trends reported in the general population. The mechanism(s) underlying improved survival require further study.
Keywords: clinical research; practice; infection and infectious agents; viral; infectious disease; organ transplantation in general; quality of care; care delivery